Topography of superior oblique muscle’s insertion to the sclera (Ukrainian Journal of Ophthalmology, 2026)
Background. Object’s localization on the surface of the eyeball is traditionally performed by measuring the distance to other objects. These measurements are made in linear values either straight on the eyeball surface. However, the size of the eyeball in every individual is different depending on the age and refraction. When using only linear measurements, it is impossible to localize correctly any given object on the eyeball surface without regard to the eye’s size. As a rule, all distances are given for an average size eye of an adult, 12 mm in radius. Since the sizes of eyeballs of patients, especially of children, are varied depending on the age and refraction, corresponding tables of distances should be done for different eyeball sizes when localizing the zones of insertion of extraocular muscles.The purpose of the present paper was to specify the localization of superior oblique muscle’s insertion to the sclera using spherical coordinate system.Materials and Methods. 24 eyes of 19 patients were examined. Radius of the eyeballs ranged from 9.5 to 12.5 mm. The examinations were performed during strabismus surgeries. To transform the linear values into spherical coordinates, “Computed software for calculating the coordinates of objects on the surface of the eyeball model" was used. To map out anatomical formations on the eyeball surface, we created a map of the eyeball surface in rectangular cylindrical projection of ophthalmographical spherical coordinate system (OSCC).Results. Superior oblique muscles insertion sites are localized between 340° and 30° longitude and between 25° and -65° latitude. However, the major area of superior muscle insertion is between 350° and 25° longitude and between 10° and -50° latitude. Herewith, the anterior border of insertion area is mainly located within the range between 10° and 25° longitude and posterior border are scattered from 350° and 15° longitude. As for latitude, it is even more variable: there are both extremely anterior and extremely posterior variants of insertion. The relative longitude of the insertion site is also widely ranged.Conclusions. The use of ophthalmographic spherical coordinate system enables to standardize the localization of superior oblique muscle insertion sites without regard to the size of the eyeball.The possible localization of the superior oblique muscle insertion to the sclera was admeasured within the range mainly between 340° and 30° longitude and 25° and -65° latitude.
Keywords: superior oblique muscles; insertion; Spherical coordinate system; mapping of the eyeball surface